276 Repeated Measures of PAP at Different Elevations in Beef Bulls in Colorado. (30th November 2020) - Zimprich, Taylor R; Speidel, Scott; Schafer, David; LaShell, Beth; Holt, Tim; Enns, Mark; Cunningham, Sam; Thomas, Milt
Abstract: High Mountain Disease (HMD) in cattle is a consequence of altitude-induced (> 1500 m) pulmonary hypertension (PH). Pulmonary arterial pressure (PAP; mmHg) is an indicator of PH-HMD and moderately heritable. This study analyzed repeated measures of PAP in growing bulls and estimated correlations across elevations and ages. Data included breed, PAP, elevation, weights and ages in spring-born bulls from the Agriculture Research, Development, and Education Center (ARDEC) in Colorado. Five PAP measurements were collected from each bull: 1) Weaning PAP at ARDEC (1, 525 m); 2) Yearling PAP at ARDEC (i.e., gain-test); 3) PAP after acclimating for 28 days at Fort Lewis College (FLC; 2, 470 m); 4) before returning to ARDEC from FLC after 110 days of grazing; and 5) after re-acclimating for 57 days to the moderate elevation and feeding systems at ARDEC when bulls were 18 months of age. Across these 5 times in Angus (n = 18) and Hereford (n = 12) bulls, PAP measures were: 1) 37.97 ± 0.37; 2) 40.93 ± 0.77; 3) 46.10 ± 1.48; 4) 45.00 ± 1.11; and 5) 42.23 ± 0.67, respectively. Breed and elevation-age were important (P < 0.05) sources of variation. Also, PAP changed (P < 0.05) across the 5 time periods (i.e., increased with altitude and then declined as bulls returned to moderate altitude). Yearling PAP measurements collected at 1, 525 m were highly correlated with PAP measures at 2, 470 m, as well as a PAP collected at 18.3 ± 0.1 mo of age at 1, 525 m (r = 0.93 to 0.99); therefore, suggesting that the yearling PAP measurement collected at 1, 525 m in gain-tested bulls was an adequate predictor of PAP at elevations of 1, 525 and 2, 470 m as bulls aged to 18 months; however, additional study of bovine PAP across elevations, ages, and rates of gain is warranted.